Three-dimensional clinical handheld photoacoustic/ultrasound scanner - Lee, Changyeop (Photoacoustics, 2020)
Clinical 2D photoacoustic (PA) imaging can be easily implemented in a traditional ultrasound (US) system. However, 3D PA imaging is still preferable because 2D B-mode PA/US imaging suffers from low reproducibility and high-operator dependency. Here, we demonstrate a compact clinical handheld 3D PA/US scanner using an 1D linear array US transducer combined with a mechanical scanning stage working via a Scotch yoke mechanism. The entire scanner measures just 100 × 80 × 100 mm(3) and weighs only 950 g, so it can easily be operated by hand. Blood vessels and hemoglobin oxygen saturation images of different parts of the human body (e.g., neck, wrist, thigh, and instep) have been successfully acquired. The system can potentially be used for clinical applications in fields such as oncology, dermatology, nephrology, and internal medicine.